Combination of Melolabial Interpolation Flap and Nasal Sidewall and Cheek Advancement Flaps Allows for Repair of Complex Compound Defects. Issue 6 (June 2018) - Patel, Payal M.; Greenberg, Judah N.; Kreicher, Kathryn L.; Burkemper, Nicole M.; Bordeaux, Jeremy S.; Maher, Ian A.
Abstract : BACKGROUND: The paramedian forehead flap (PMFF) is the repair of choice for large nasal defects involving multiple cosmetic subunits. However, the PMFF may not be optimal for all patients. The combination of a melolabial interpolation flap (MLIF) and a nasal sidewall flap may serve as an alternative. OBJECTIVE: To present the surgical technique and aesthetic outcomes of the alternative reconstruction for surgical defects of the lower nose. MATERIALS AND METHODS: Fourteen patients with multisubunit nasal Mohs defects reconstructed alternatively were identified from 2 academic centers in this retrospective case series. Illustrations and photographs were used to demonstrate surgical technique and outcomes. Final aesthetic results were analyzed using the Patient and Observer Scar Assessment Scale. RESULTS: The physician observer rated the scar outcome a mean score of 10.9 ± 3.3. Patients rated their results as a mean of 9.1 ± 4.7. The mean "Patient" Overall Opinion score was 2.3 ± 2.6 and the mean "Observer" Overall Opinion score was 1.9 ± 0.9. No patients reported problems with nasal airflow or obstruction, and cosmetic complications such as pincushioning or alar buckling were not observed. CONCLUSION: The combined MLIF and nasal sidewall flap is an alternative repair for complex distal nasal defects. Abstract : Supplemental Digital Content is Available in the Text.